Where fast weathering creates thin regolith and slow weathering creates thick regolith. Issue 8 (28th December 2012) - Bazilevskaya, Ekaterina; Lebedeva, Marina; Pavich, Milan; Rother, Gernot; Parkinson, Dilworth Y.; Cole, David; Brantley, Susan L.
ABSTRACT Weathering disaggregates rock into regolith – the fractured or granular earth material that sustains life on the continental land surface. Here, we investigate what controls the depth of regolith formed on ridges of two rock compositions with similar initial porosities in Virginia (USA). A priori, we predicted that the regolith on diabase would be thicker than on granite because the dominant mineral (feldspar) in the diabase weathers faster than its granitic counterpart. However, weathering advanced 20× deeper into the granite than the diabase. The 20 × ‐thicker regolith is attributed mainly to connected micron‐sized pores, microfractures formed around oxidizing biotite at 20 m depth, and the lower iron (Fe) content in the felsic rock. Such porosity allows pervasive advection and deep oxidation in the granite. These observations may explain why regolith worldwide is thicker on felsic compared to mafic rock under similar conditions. To understand regolith formation will require better understanding of such deep oxidation reactions and how they impact fluid flow during weathering. Copyright © 2012 John Wiley & Sons, Ltd.